A Derivative-Free Liu–Storey Method for Solving Large-Scale Nonlinear Systems of Equations. (29th October 2020) - Su, Zhenhua; Li, Min
Abstract : In this paper, a descent Liu–Storey conjugate gradient method is extended to solve large-scale nonlinear systems of equations. Based on certain assumptions, the global convergence property is obtained with a nonmonotone line search. The proposed method is suitable to solve large-scale problems for the low-storage requirement. Numerical experiment results show that the new method is practically effective.